Giftedness and academic motivation in GenAI contexts: the moderating and mediating role of gender and AI anxiety - Mohamed, Amr Mahmoud; Emran, Abdul Qader; Abdelrady, Abbas Hussein; Deen, Abdul Aziz Mohamed Mohamed Ali El (Frontiers in Education, 2026)
IntroductionThis study investigated the relationships among gifted behavior, Generative AI (GenAI) anxiety, and learning motivation among gifted EFL university students in Saudi Arabia, with an additional focus on the mediating role of GenAI anxiety and the moderating effect of gender.MethodsUsing a quantitative correlational design, data were collected from 304 purposively selected undergraduates classified as gifted based on institutional records and psychometric confirmation using Gifted Rating Scales. The participants answered the verified instruments of gifted behavior, GenAI anxiety, and academic motivation.ResultsAnalysis of structural equation modeling showed that gifted behavior was associated with lower GenAI anxiety and higher motivation, and that GenAI anxiety had a significant negative association with motivation. The mediation analysis indicated that the relationship between gifted behavior and motivation was partially mediated by GenAI anxiety. Gender was a significant moderator of the relationships between gifted behavior and motivation, as well as between GenAI anxiety and motivation, with both associations being stronger among females.DiscussionThe findings contribute to the growing body of research on the psychological impact of AI implementation in EFL learning, suggesting that gifted learners’ responses to GenAI technologies are characterized by distinct affective and motivational patterns. The research provides theoretical insights into giftedness and technology-related emotions, providing pedagogical implications for creating AI-based EFL learning environments that are sensitive to learners’ cognitive and affective profiles.